Chronic differences in white matter integrity following sport‐related concussion as measured by diffusion MRI: 6‐Month follow‐up. Issue 11 (2nd July 2018) - Lancaster, Melissa A.; Meier, Timothy B.; Olson, Daniel V.; McCrea, Michael A.; Nelson, Lindsay D.; Muftuler, L. Tugan
Abstract: Recent studies demonstrated evidence of physiological changes in the brain following sport‐related concussion (SRC) that persisted beyond the point at which athletes achieved full symptom recovery. Diffusion MRI techniques have been used to study brain white matter (WM) changes following SRC; however, longitudinal studies that follow injured athletes from the acute to chronic stages of injury are sparse. The current study explores potential persisting effects of the injury, which serves as a follow‐up to our previous work that reported WM changes in the acute and subacute phase of SRC recovery. Concussed high school and collegiate football players ( n = 17) and well‐matched teammate controls ( n = 20) were followed up at 6 months postinjury with diffusion tensor (DTI) and diffusion kurtosis imaging (DKI) as well as measures of self‐reported symptoms, cognitive functioning, and balance. Results of tract‐based spatial statistics (TBSS) analyses revealed continued widespread decreased mean and axial diffusivity compared to control subjects in 6‐month follow‐up scans. On the other hand, kurtosis metrics, which were significantly higher in concussed athletes in the acute phase, had normalized. WM tract regions‐of‐interest (ROIs) were created from significant clusters in the TBSS analysis, and linear mixed effects (LME) analyses were used to look at longitudinal changes in these ROIs over time. LME analyses revealed few time × group interactions indicating findings were relatively stable over time. In addition, acute concussion symptoms predicted diffusivity measures at 6 months postinjury. Findings indicate that DTI and DKI may be useful tools in assessing concussion severity, recovery, and possible long‐term effects of concussion.